2013
DOI: 10.1007/s10571-013-9973-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Bacopa monnieri and Bacoside A Against Dopamine Receptor Dysfunction in the Cerebral Cortex of Neonatal Hypoglycaemic Rats

Abstract: Neonatal hypoglycaemia initiates a series of events leading to neuronal death, even if glucose and glycogen stores return to normal. Disturbances in the cortical dopaminergic function affect memory and cognition. We recommend Bacopa monnieri extract or Bacoside A to treat neonatal hypoglycaemia. We investigated the alterations in dopaminergic functions by studying the Dopamine D1 and D2 receptor subtypes. Receptor-binding studies revealed a significant decrease (p < 0.001) in dopamine D1 receptor number in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Nesfatin-1, expressed also in neurones of various brain areas, including the hypothalamic and brainstem nuclei, is an 82 amino-acid peptide originated from post-translational processing of the N-terminal fragment of nucleobindin 2 (NUCB2) (Finelli et al 2014). Some results suggest that (i) a subpopulation of nesfatinergic neurones belongs to the central network activated by hypoglycemia and that nesfatin-1 participates in the triggering of physiological and hormonal counter-regulations observed in response to hypoglycemia (Bonnet et al 2013); (ii) in the rat experimental model of neonatal hypoglycemia, Bacopa extract improved alterations in D1 and D2 receptor expressions, cAMP signalling, and cell death resulting from oxidative stress (Thomas et al 2013). Disturbances in the cortical dopaminergic function affect memory and cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesfatin-1, expressed also in neurones of various brain areas, including the hypothalamic and brainstem nuclei, is an 82 amino-acid peptide originated from post-translational processing of the N-terminal fragment of nucleobindin 2 (NUCB2) (Finelli et al 2014). Some results suggest that (i) a subpopulation of nesfatinergic neurones belongs to the central network activated by hypoglycemia and that nesfatin-1 participates in the triggering of physiological and hormonal counter-regulations observed in response to hypoglycemia (Bonnet et al 2013); (ii) in the rat experimental model of neonatal hypoglycemia, Bacopa extract improved alterations in D1 and D2 receptor expressions, cAMP signalling, and cell death resulting from oxidative stress (Thomas et al 2013). Disturbances in the cortical dopaminergic function affect memory and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Wistar neonatal rats used for the experiments were grouped into two groups as follows: (i) control (C), control rats were injected with saline, subcutaneously for 10 days starting from P7; (ii) hypoglycemic (H), hypoglycemic rats received human regular insulin (Actrapid) at a dosage of 10 IU·(kg body mass) −1 ·day −1 subcutaneously and fasted for 240 min in the presence of foster mother (Thomas et al 2013). The animals were injected once daily for 10 days from postnatal day 7 to postnatal day 17 (i.e., P7 to P17; Table 1).…”
Section: Induction Of Hypoglycemia In Neonatal Ratsmentioning
confidence: 99%
“…Many plant species in diverse regions of the world have been screened for their neuroprotective activity. Extracts of plants such as Green tea (Cho et al 2008), Tripterygium regelii (Choi et al 2010), Rhus verniciflua (Sapkota et al 2011), Eucommia ulmoides (Kwon et al 2012), Hyptis suaveolens (Ghaffari et al 2014), Bacopa monnieri (Thomas et al 2013), and Cyperus rotundus ) were reported to possess antioxidant properties and neuroprotective effects. However, there are very few reports on the neuroprotective compounds of fungal origin.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Bacoside A is the main bioactive component and consists of a mixture of saponins (Bacoside A3, bacopaside II, jujubogenin isomer of bacopasaponin C and bacopasaponin C) [52]. Several experimental studies have demonstrated the neuro-protective properties of Bacopa monnieri such as regulation of cholinergic system, enhancing acetylcholine levels, reducing neuroinflammation, amyloid levels and oxidative stress [52][53][54][55][56][57]. Hippophae rhamnoides, commonly known as sea buckthorn or amlavetas, also has been traditionally used for its medicinal properties [58].…”
Section: Discussionmentioning
confidence: 99%